ECONOMIC PROGRESS AND THOUGHT: THE LEGACY OF SHAHU MAHARAJA IN KOLHAPUR (International Journal of Food and Nutritional Sciences, 2021)
Shahu Maharaja of Kolhapur demonstrated a profound commitment to economic development from the early days of his reign. Faced with challenges such as debt-ridden farmers and the repercussions of the plague and famines between 1896 and 1899, he sought innovative solutions to revitalize Kolhapur’s economy. His 1902 visit to England during King Edward VII's Coronation Ceremony exposed him to the benefits of industrialization, inspiring him to introduce similar advancements in Kolhapur. In 1906, he inaugurated the state’s first Cotton Mill, underscoring the importance of local cooperation in industrial growth. His approach integrated industrial and agricultural development, advocating for educational reforms, cooperative movements, and infrastructural projects like the Radhanagari Dam. These initiatives significantly improved the livelihoods of Kolhapur’s residents and set a progressive precedent for economic policies in India.